Are Cross-Sectional Imaging Modalities Enough for Sarcopenia Assessment? - , Haluk Tarık Kani, Elif Tufan (Turkish Journal of Gastroenterology 1, 2024)
Cite this article as: Kani HT, Tufan E. Are cross-sectional imaging modalities enough for sarcopenia assessment? Turk J Gastroenterol. 2024;35(1):73-74.